Ag distribution and corrosion behaviour of the plasma electrolytic oxidized antibacterial Mg-Ag alloy. (10th April 2022) - Zhang, Yupeng; Li, Yong; Lv, You; Zhang, Xinxin; Dong, Zehua; Yang, Lei; Zhang, Erlin
Highlights: Both metallic Ag and Ag oxide exist in the coating. A nano-sized Ag-rich layer exists at the substrate/coating interface. PEO affects corrosion morphology and susceptibility of Mg-Ag alloy. A sustained Ag + release is achieved after PEO of Mg-Ag alloy. Abstract: The application of biodegradable Mg alloys as implanted devices has been hindered by their low corrosion resistance and potential risk associated with microbial infection. In the present work, a rolled Mg-Ag alloy was studied, which was subjected to plasma electrolytic oxidation (PEO) to achieve a favoured balance between corrosion resistance and antimicrobial capability. The Ag distribution, corrosion resistance and Ag ionic release behaviour have been examined in details. It is revealed that PEO process leads to both incorporated Ag + and Ag-rich nanoparticles in forms of metallic Ag and Ag oxide across the coating. In addition, a nano-sized Ag-enriched layer also exists at the substrate/coating interface. The microstructural modification associated with PEO process results in an increased corrosion resistance and a sustained Ag ionic release, indicating that it is a promising surface modification technique for antibacterial Mg-Ag alloy. Graphical Abstract: Image, graphical abstract